Pengembangan Virtual Reality Untuk Mendigitalisasi Situs Peninggalan Sejarah Masjid Agung Banten - Edi Junaedi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
In this modern period almost all of our activities can not be separated from the name of technology, technological development is a major factor that affects every human element. One of them in the ﬁeld of architecture and tourism that has been utilizing digital technology to perform various activities. Virtual Reality is the latest technology that can generate realistic three- dimensional atmosphere, and can make users interact with the virtual envi- ronment. Virtual Reality is an exciting technology that can fundamentally change how we interact with information. In this writing, the author uses Virtual Reality technology to create a place that is in Banten, Banten Grand Mosque that will run on the PC.The author uses SketchUp and Unity applications to build 3D building objects and make them into Virtual Reality applications. Keywords: Applications, Banten, Banten Great Mosque, Virtual Reality